2016
DOI: 10.21859/sija-1103466
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fall and Its Related Factors Among Older People in Bojnurd in 2015

Abstract: Objectives Falls are a major health problem and a leading cause of injury-related death and disabilities in the elderly. Therefore, the aim of this study was to survey fall prevalence and its related factors among the elderly in Bojnurd. Methods & Materials This cross-sectional study was performed on 288 elderly residents in Bojnurd in 2015. By strata sampling, the elderly people were included in the study according to their population in each stratum by randomization. Data was collected by a self-made checkli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 2 publications
2
25
0
1
Order By: Relevance
“…Our study found that more than three quarters of the participants’ falls occurred at home. This finding is similar to those of other studies . Some studies have found that a larger proportion of falls occur away from the home environment .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study found that more than three quarters of the participants’ falls occurred at home. This finding is similar to those of other studies . Some studies have found that a larger proportion of falls occur away from the home environment .…”
Section: Discussionsupporting
confidence: 92%
“…Most previous studies have examined the falls in those aged over 60 or 65. Community‐based studies of individuals aged 60 or over have found fall frequencies ranging from 11.3% to 44.5% . According to the WHO Global Report, 28%‐35% of people aged 65 and over fall each year, and this rate increases to 32%‐42% for those over 70 years of age .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations